The Role of the Unfolded Protein Response on Renal Lipogenesis in C57BL/6 Mice - Elizabeth Figueroa-Juárez; Lilia G. Noriega; Carlos Pérez-Monter; Gabriela Alemán; Rogelio Hernández-Pando; Ricardo Correa-Rotter; Victoria Ramírez; Armando R. Tovar; Iván Torre-Villalvazo; Claudia Tovar-Palacio (Biomolecules, 2021)
Renal injury observed in several pathologies has been associated with lipid accumulation in the kidney. While it has been suggested that the accumulation of renal lipids depends on free fatty acids released from adipose tissue, it is not known whether in situ renal lipogenesis due to endoplasmic reticulum (ER) stress contributes to kidney injury. The aim of the present study was to elucidate the role of pharmacological ER stress in renal structure and function and its effect on renal lipid metabolism of C57BL/6 mice. ER stress increased serum creatinine and induced kidney structural abnormalities. Tunicamycin-administered mice developed hyperinsulinemia, augmented lipolysis and increased circulating leptin and adiponectin. Renal unfolded protein response (UPR) gene expression markers, the lipogenic transcription factor SREBP1 and the phosphorylation of eIF2α increased 8 h after tunicamycin administration. At 24 h, an increase in BiP protein content was accompanied by a reduction in p-eIF2α and increased SREBP-1 and FASn protein content, in addition to a significant increase in triglyceride content and a reduction in AMPK. Thus, ER stress induces in situ lipid synthesis, leading to renal lipid accumulation and functional alterations. Future pharmacological and/or dietary strategies must target renal ER stress to prevent kidney damage and the progression of metabolic diseases.